The RELATIONSHIP OF COMMON COLD KNOWLEDGE LEVEL WITH COMMON COLD SELFMEDICATION BEHAVIOR IN NON-HEALTH FACULTY STUDENTS AT MUHAMMADIYAH UNIVERSITY, YOGYAKARTA - Utami, Pinasti (Pharmaceutical Journal of Indonesia, 2023)
According to the 2016 National Health Survey, 72.44 percent of people self-medicate, and according to the Bantul District Health Office's 2019 Health Profile, acute nasopharyngitis (common cold) was among the top 10 disorders with 84,142 patients. Self-medication must be accompanied by sound knowledge in order for treatment to be effective and sensible. The goal of this study was to see if there's a link between having a good understanding of the common cold and self-medication for the common cold in non-health faculty students at the University of Muhammadiyah Yogyakarta. The common cold knowledge level questionnaire and the common cold self-medication behavior questionnaire were used in this study. The Spearman rank correlation test was used to analyze the data. According to the findings of this study, respondents' degree of knowledge on self-medication for the common cold is known, with 84.5 percent of respondents falling into the category of good knowledge and 15.5 percent falling into the category of sufficient knowledge. 82.3 percent of respondents are in the good conduct category, 12.5 percent are in the moderate behavior area, and 5.4 percent are in the poor behavior category when it comes to common cold self-medication activity. The correlation test revealed a significant correlation value (p-value 0.005) and a correlation coefficient of 0.141 between knowledge level and self-medication behavior. Based on the findings, it can be inferred that there is a link between common cold knowledge and self-medication behavior in non-health faculty students at the University of Muhammadiyah Yogyakarta.